Respuesta :

Answer:

Choose some points for x to find its y, the f(x).

To find its inverse, switch the x and y coordinates.

y = 3x + 1

y = 3(-3) + 1

y = -8

f(x) (-3, -8)

f⁻¹(x) (-8, -3)

y = 3x + 1

y = 3(-2) + 1

y = -5

f(x) (-2, -5)

f⁻¹(x) (-5, -2)

y = 3x + 1

y = 3(-1) + 1

y = -2

f(x) (-1, -2)

f⁻¹(x) (-2, -1)

y = 3x + 1

y = 3(0) + 1

y = 1

f(x) (0, 1)

f⁻¹(x) (1, 0)

y = 3x + 1

y = 3(1) + 1

y = 4

f(x) (1, 4)

f⁻¹(x) (4, 1)

y = 3x + 1

y = 3(2) + 1

y = 7

f(x) (2, 7)

f⁻¹(x) (7, 2)

y = 3x + 1

y = 3(3) + 1

y = 10

f(x) (3, 10)

f⁻¹(x) (10, 3)

ACCESS MORE